Objective versus Subjective Performance Evaluations - Stefan Terstiege (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
Why does incentive pay often depend on subjective rather than objective performance evaluations? After all, subjective evaluations entail a credibility issue. While the most plausible explanation for this practice is lack of adequate objective measures, I argue that subjective evaluations might sometimes also be used to withhold information from the worker. I furthermore argue that withholding information is particularly important under circumstances where the credibility issue is small. The statements are derived from a two-stage principal-agent model in which the stochastic relationship between effort and performance is unknown.
urn:nbn:de:bvb:19-epub-17335-1
Keywords: D83; D86; M12; M52; 330; Performance evaluation; principal-agent; moral hazard